2016
DOI: 10.1021/acssensors.6b00533
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Sensing Difluoroboron β-Diketonate Polylactide Materials with Tunable Dynamic Ranges for Wound Imaging

Abstract: Difluoroboron β–diketonate poly(lactic acid) materials exhibit both fluorescence (F) and oxygen sensitive room-temperature phosphorescence (RTP). Introduction of halide heavy atoms (Br and I) is an effective strategy to control the oxygen sensitivity in these materials. A series of naphthyl-phenyl (nbm) dye derivatives with hydrogen, bromide and iodide substituents were prepared for comparison. As nanoparticles, the hydrogen derivative was hypersensitive to oxygen (0–0.3%), while the bromide analogue was suite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 62 publications
(162 reference statements)
0
85
0
Order By: Relevance
“…In the general process, an organic molecule is excited from the ground state (S 0 ) to the excited singlet state (S n , n ≥1), which is allowed because of the same spin value (step 1). On the contrary, the S 1 →T 1 ISC process (step 2) is often spin‐forbidden for metal‐free organic molecules and is mostly promoted by mixing the singlet–triplet states of different molecular orbital configurations (El‐Sayed rule; for example, aromatic carbonyls), by decreasing the singlet–triplet splitting energy (Δ E ST ) through intramolecular charge‐transfer (ICT) interactions, and by introducing the heavy‐atom effect . Then the phosphorescence process occurs if the T 1 state undergoes radiative decay to the ground state (step 3) .…”
Section: Factors Governing Rtpmentioning
confidence: 99%
“…In the general process, an organic molecule is excited from the ground state (S 0 ) to the excited singlet state (S n , n ≥1), which is allowed because of the same spin value (step 1). On the contrary, the S 1 →T 1 ISC process (step 2) is often spin‐forbidden for metal‐free organic molecules and is mostly promoted by mixing the singlet–triplet states of different molecular orbital configurations (El‐Sayed rule; for example, aromatic carbonyls), by decreasing the singlet–triplet splitting energy (Δ E ST ) through intramolecular charge‐transfer (ICT) interactions, and by introducing the heavy‐atom effect . Then the phosphorescence process occurs if the T 1 state undergoes radiative decay to the ground state (step 3) .…”
Section: Factors Governing Rtpmentioning
confidence: 99%
“…These are important considerations for tailoring the sensitivity and designing fluorophores for lifetime imaging, such as fluorescence lifetime imaging microscopy (FLIM) and phosphorescence lifetime imaging microscopy (PLIM) . For lifetime‐based imaging, sensors like BF 2 nbmPLA, a compound with similar properties to compounds 1 and 3 in this study with long phosphorescence lifetimes, can be dynamically quenched by oxygen more quickly, and exhibit a linear response to O 2 within a small range (0.0–0.3 % O 2 ) The large Stern–Volmer constant makes the sensors sensitive to minor changes in O 2 concentration. This type of sensor may be suitable for measurements in environments depleted of oxygen, such as tumors .…”
Section: Resultsmentioning
confidence: 97%
“…This type of sensor may be suitable for measurements in environments depleted of oxygen, such as tumors . Shorter phosphorescence lifetime sensors such as BF 2 nbm(Br)PLA, analogous to compound 2 , with a broader linear sensing range (0–3 %) are capable of monitoring O 2 in environments more rich in oxygen, such as wounds and tissues …”
Section: Resultsmentioning
confidence: 99%
“…Even though intense luminescence can be observed in the solution state, optical properties were often spoiled through ACQ by intermolecular interactions in the solid state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%